Analysis of Legal Studies on The Implementation of Qardh Bisyarti Rahni Products At KSPPS BMT USA Jepara - Rokhimah, Rokhimah; Ansori, Miswan (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2024)
This study aims to analyze the legal review of the implementation of the Qardh Bisyarti Rahni product at KSPPS BMT USA Jepara. In addition, this study is expected to provide a better understanding of the efforts that need to be made to ensure legal compliance and operational sustainability of Islamic microfinance institutions. Qardh Bisyarti Rahni is one of the Islamic financial products implemented in Islamic microfinance institutions, which provides usury-free financing for the community. This study is important to ensure that the implementation of this product is in accordance with Islamic principles and does not violate applicable legal provisions. The approach used in this study is qualitative with a case study method. Data were collected through observation, interviews, and analysis of related documents. The results of the study indicate that the implementation of the Qardh Bisyarti Rahni product at KSPPS BMT USA Jepara has complied with applicable legal provisions and Islamic principles. However, there are several challenges that need to be considered, such as a lack of in-depth understanding of the legal aspects of Islamic law and changes in regulations related to Islamic finance.